Structure-guided discovery of a novel, potent, and orally bioavailable 3, 5-dimethylisoxazole aryl-benzimidazole BET bromodomain inhibitor. Issue 3 (1st February 2019) - Sperandio, David; Aktoudianakis, Vangelis; Babaoglu, Kerim; Chen, Xiaowu; Elbel, Kristyna; Chin, Gregory; Corkey, Britton; Du, Jinfa; Jiang, Bob; Kobayashi, Tetsuya; Mackman, Richard; Martinez, Ruben; et al.
Graphical abstract: Highlights: The structure-guided discovery of a novel BET bromodomain inhibitor is disclosed. The lead properties were optimized using in-vitro assays and in-vivo PK studies. The lead compound reduced the in vivo tumor growth two xenograft models. Abstract: The bromodomain and extra-terminal (BET) family of proteins, consisting of the bromodomains containing protein 2 (BRD2), BRD3, BRD4, and the testis-specific BRDT, are key epigenetic regulators of gene transcription and has emerged as an attractive target for anticancer therapy. Herein, we describe the discovery of a novel potent BET bromodomain inhibitor, using a systematic structure-based approach focused on improving potency, metabolic stability, and permeability. The optimized dimethylisoxazole aryl-benzimidazole inhibitor exhibited high potency towards BRD4 and related BET proteins in biochemical and cell-based assays and inhibited tumor growth in two proof-of-concept preclinical animal models.